PENGARUH PERBANDINGAN SARI EDAMAME (Glycin Max L. Merrill) DENGAN SARI BLACK MULBERRY (Morus nigra L.) DAN KONSENTRASI PENSTABIL TERHADAP KARAKTERISTIK MINUMAN EDAMUBERRY - Asep Dedy Sutrisno (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
The purpose of this research was to determine the effect of edamame juice ratio with black mulbery juice and concentration of stabilizer to the characteristics of Edamuberry beverage. The Research consist of two stages : preminary research and main research. The main research conducted is to make Edamuberry beverage by using stabilizer that has been obtained form preliminary research. This research design was used factorial pattern 3x3 in Randomized Block Design (RBD), which consists of two factors. The ratio of edamame juice to black mulber y juice of three levels are 1:2, 1,5:1,5, 2:1 and concentration of stabilizer of three levels are 0,1%, 0,2% and 0,3%. The response in the research was flavor, colour, taste, protein content of the kjedahl method, vitamin C content iodimetry method, and viscosity with viscometer. The result of preliminary research showed that Edamuberry beverage with additions CMC stabilizer prefered by consumers and have viscosity 145 mPas, stability 13,7oBrix, and pH 5,9. The result of main research were showed that : the ratio of edamame juice to black mulbery juice affected the colour, taste, protein content, vitamin C content and viscosity but does not affected flavor. CMC concentration affected the colour, taste and viscosity. The interaction ratio of edamame juice to black mulbery juice and CMC concentration affect to colour, taste and viscosity. The selected sample in the main research is a1b1 (ratio of edamame juice to black mulbery juice 1:2 and CMC concentration 0,1%) with a protein content 3,301%, vitamin C content 27,007 mg/100g and viskosity 91,667 mPas.